Identifying Gaps in Science Curriculum Student Learning Outcomes and Grade V Students’ Achievement - Khubaib Ahmed; Iqra Nazish; Tajammal Hussain; Yasir Abbas; Muhammad Haseeb; Sheema khan (Indus Journal of Social Sciences, 2025)
This study investigates the gaps between Science Curriculum Student Learning Outcomes (SLOs) and Grade V students’ achievement in Punjab, Pakistan, using a mixed-methods approach, analyzing Punjab Examination Commission (PEC) data (2018–2023) and teacher surveys (N=350). Results reveal significant disparities, with students achieving only 42.7% overall proficiency, while rural students underperformed urban peers by 19.5 percentage points. The weakest SLOs included Electricity & Magnetism (32.5% proficiency), Microorganisms (38.1%), and Forces & Machines (36.7%), whereas stronger performance was observed in Flowering Plants (64.2%) and the Solar System (61.8%). Key contributing factors were teacher training gaps (72% lacked inquiry-based pedagogy training), textbook misalignment (58% of SLOs not covered), and resource shortages (85% of schools without science labs). Regression analysis confirmed locale (β = -0.23, p < 0.01) and teacher training (β = 0.31, p < 0.001) as significant predictors of achievement. Qualitative findings highlighted over-reliance on rote learning and inadequate assessment feedback as systemic barriers. The study recommends SLO-aligned teacher training, revised textbooks emphasizing higher-order thinking, and equitable lab resource distribution to bridge these gaps, providing actionable insights for policymakers to enhance science education efficacy in Pakistan and similar contexts.